Dialog z tradycją literacką w wierszach kresowych z tomu De profundis Wojciecha Wencla - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Eastern Borderlands are present in the consciousness of those who used to live there, but also those who revive their - sometimes very painful - memory. Such is the case of the poems by Wojciech Wencel, who is not afraid to open the tragic pages of history. His lyric poetry is not just a chronicle of Polish martyrisation. It is also a proof of profound literary culture and influence of tradition. The article mentions various levels of intertextual games, played by the poet in his borderland poems from De profundis - the collection with a meaningful title, derived from the Bible.
Keywords: poezja; Kresy Wschodnie; tradycja literacka; intertekstualność; melodyjność; poetry; Eastern Borderlands; literary tradition; intertextuality; melodiousness